2013
DOI: 10.1080/00071668.2013.770128
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of the CAPN1 gene is associated with meat quality traits in Japanese quail

Abstract: 1. The objective of the study was to investigate the polymorphisms in two regions of the calpain 1 (CAPN1) gene and their association with breast and thigh meat quality in Japanese quail (ultimate pH (pHu), lightness, redness, yellowness, drip loss, thawing-cooking loss, water holding capacity and shear force, SF). 2. Blood samples were collected randomly from 100 birds and DNA was extracted using a commercial kit. Genotypes were determined by PCR amplification followed by single-strand conformation polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In this study, a genetic variant as g.103969C>T in the 4 th exon region and eight novel SNPs are identified as g.104116A>T, g.104118T>G, g.104148G>C, g.104169G>C, g.104172A>G, g.104179C>G, g.104181G>A, g.104184T>C in the 5 th exon region of CAPN1 gene in Japanese quail. Rasouli et al (2013) found that the genotypes of the CAPN1 gene in the 217-bp region were significantly related with yellowness and shear force. Soria et al (2009) and Smith et al (2009) reported similar findings and declared that when the myoglobin content of breast muscle was low, the yellowness of the meat could increase.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In this study, a genetic variant as g.103969C>T in the 4 th exon region and eight novel SNPs are identified as g.104116A>T, g.104118T>G, g.104148G>C, g.104169G>C, g.104172A>G, g.104179C>G, g.104181G>A, g.104184T>C in the 5 th exon region of CAPN1 gene in Japanese quail. Rasouli et al (2013) found that the genotypes of the CAPN1 gene in the 217-bp region were significantly related with yellowness and shear force. Soria et al (2009) and Smith et al (2009) reported similar findings and declared that when the myoglobin content of breast muscle was low, the yellowness of the meat could increase.…”
Section: Discussionmentioning
confidence: 97%
“…Primer sequences of CAPN1 gene was designed based on the quails sequence retrieved from GenBank (Accession number NW_015439879.1) using Primer-BLAST algorithm (https:// www.ncbi.nlm.nih.gov/tools/primer-blast/). Primer sequences of CAPN1 gene are F: 5′-TGG AGT GCT TTG CTG GAG AAA GCC TA-3 and R: 5′-TGG TAG AGG TCT GCG GGG GGC TTG CG-3′ (Rasouli et al, 2013). The 25 µL PCR volume contained: 50 ng genomic DNA, 0.5 µM of each primers, 1× PCR Buffer, 200 µM dNTP, 2 mM MgCl2 and 1 U of Taq DNA polymerase (Invitrogen, Life Technologies).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Okumura et al [ 38 ] identified four calpain genes (i.e., CAPN1 , CAPN2 , CAPN3 , and CAPN1.5 ) that were ubiquitously expressed in chickens. Among these, a single nucleotide polymorphism (SNP) in the CAPN1 gene was significantly related to meat tenderness in chickens and Japanese quail [ 10 , 39 ]. Moreover, Piórkowska et al [ 40 ] found that higher expression of the CAPN1 gene leads to higher tenderness in breast muscles in fast-growing broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the issues of selecting the most favorable quail populations for egg production are mandatory. So that, several candidate genes have been selected and considered as a basis for market-associated selection and their association with the main productive traits has been analyzed [ 6 , 7 ]. In addition, a number of genomic regions linked to the production traits in Japanese quail have been identified using linkage analyses [ 8 – 11 ].…”
Section: Introductionmentioning
confidence: 99%